Nodular Lymphocyte Predominant Hodgkin’s Lymphoma with T Cell/ Histiocyte Rich Large B Cell Lymphoma Like Transformation - Batra, Sakshi; Batra, Harsh; Ahluwalia, Charanjeet; Ranga, Sunil (Annals of Pathology and Laboratory Medicine, 2020)
Nodular lymphocyte predominant Hodgkin’s lymphoma (NLPHL) is an uncommon variant form of Hodgkin’s lymphoma with a worldwide incidence of 5%. 1 It has long been recognized that NLPHL can have varied growth patterns, including some with diffuse areas and/or numerous T cells.2 NLPHL may evolve to a completely diffuse T-cell–rich proliferation lacking any follicular dendritic cells which would be consistent with a T-cell histiocyte-rich large B-cell lymphoma (THRLBCL) or can be associated with such a proliferation at a separate site. Recent data indicate that progression to a process with features of THRLBCL is associated with a more aggressive clinical course, and requires different management, hence the significance of diagnosing correctly THRLBCL-like transformation of NLPHL. We report a case of THRLBCL-like transformation of NLPHL in an 11-year old male child.